Pediatric Cardiovascular Drug Trials, Lessons Learned - Li, Jennifer S. (2011)
Few drugs have been labeled for pediatric cardiovascular indications and many children with cardiac disease are prescribed drugs off-label. Recent initiatives have narrowed this gap and as a result there are an increasing number of cardiology trials in the pediatric population. Many studies, however, have either failed to show a dose response in children or have not shown efficacy in children when they have established efficacy in adults. Clinical trials are challenging in children; many factors such as lack of development of a liquid formulation, failure to fully incorporate pharmacokinetic information into trial design, poor dose selection, the lack of clinical equipoise, and the use of difficult surrogate and composite primary endpoints have led to the difficulties and failures observed in several pediatric cardiovascular trials. These lessons learned may help to inform future pediatric clinical trial development.